Maternal exposure to pesticides during pregnancy and risk for attention-deficit/hyperactivity disorder in offspring: A protocol for systematic review and meta-analysis. Issue 26 (2nd July 2021) - Zhu, Zhixian; Wang, Ying; Tang, Shiming; Tan, Huawei; Liu, Cheng; Cheng, Liwei
Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) is the most common psychiatric disorder in childhood. Studies explored the association of maternal exposure to pesticides during pregnancy with a risk of offspring developing ADHD, but have reported inconclusive results. Here, we will perform a systematic review and meta-analysis of observational studies to assess a possible association between them. Methods: This study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols. PubMed, Embase, Web of Science, the Cochrane Library, and the PsycINFO will be searched from inception to May 2021. Observational studies investigating the association of maternal exposure to pesticides during pregnancy with a risk of offspring developing ADHD will be considered. The Newcastle-Ottawa Scales or the scale of the Agency for Healthcare Research and Quality will be used to assess the methodological quality of the included studies according to their study design. A fixed or random-effect model will be used to synthesize data depend on the heterogeneity test. STATA version 12.0 will be used to conduct the meta-analysis. Results: This study will provide a high-quality evaluation of association between maternal exposure to pesticides during pregnancy and risk for ADHD in offspring. Conclusion: This study will present evidence on whether maternal exposure to pesticides during pregnancy is a risk factor for ADHD in offspring.